Muzakki's Decision to Pay Zakat Reviewed from Maqashid Syariah, Social Environment and Zakat Knowledge - Faisal, Yusuf; Sari, Egi Gumala (UIN Sunan Kudus, 2025)
This study aims to test, analyze, and provide empirical evidence regarding the impact of zakat knowledge, maqashid sharia, and the social environment on the decision to pay zakat in Bekasi City. A quantitative research method was employed, utilizing primary data from a sample of 1,329 individuals. Data analysis was performed using Partial Least Squares (PLS) software. The results indicate that zakat knowledge has a positive, but statistically insignificant, effect on the decision to pay zakat. In contrast, both the maqashid sharia and social environment variables show a positive and statistically significant impact on the decision to pay zakat. This study is valuable for understanding the factors that influence zakat payment decisions, as there is limited research that integrates zakat knowledge and maqashid sharia based on Islamic law. Therefore, this research not only enriches academic practices but also contributes to a more ethical understanding of Islamic law.